2015
DOI: 10.1002/anie.201410309
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Synthesis of Monodisperse Poly(ethylene glycols) and Derivatives through Macrocyclization of Oligo(ethylene glycols)

Abstract: A macrocyclic sulfate (MCS)-based approach to monodisperse poly(ethylene glycols) (M-PEGs) and their monofunctionalized derivatives has been developed. Macrocyclization of oligo(ethylene glycols) (OEGs) provides MCS (up to a 62-membered macrocycle) as versatile precursors for a range of monofunctionalized M-PEGs. Through iterative nucleophilic ring-opening reactions of MCS without performing group protection and activation, a series of M-PEGs, including the unprecedented 64-mer (2850 Da), can be readily prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 35 publications
2
66
0
Order By: Relevance
“…Recently, Jiang et al reported a novel approach towards monodisperse OEGs based on a macrocyclic monomer, which is ring‐opened upon addition of glycol . This approach is also based on bidirectional growth, meaning that the glycol adds two macrocyclic monomers in one reaction step.…”
Section: Liquid‐phase Synthesis Of Sequence‐defined Macromoleculesmentioning
confidence: 99%
“…Recently, Jiang et al reported a novel approach towards monodisperse OEGs based on a macrocyclic monomer, which is ring‐opened upon addition of glycol . This approach is also based on bidirectional growth, meaning that the glycol adds two macrocyclic monomers in one reaction step.…”
Section: Liquid‐phase Synthesis Of Sequence‐defined Macromoleculesmentioning
confidence: 99%
“…Additionally, robust synthetic methods need to be established for coupling individual monomer units, preventing access to many important monomer classes, such as acrylates, styrenics, and functional siloxanes. 2532 …”
Section: Introductionmentioning
confidence: 99%
“…The cycle is then repeated to give 6 . At this stage, the PEG is asymmetric, which is highly desirable in most applications but more challenging to make using other methods . However, if it were cleaved from the solid support, it would become symmetrical.…”
Section: Resultsmentioning
confidence: 99%
“…A significant advantage of the solid phase method is that the difficult‐to‐access asymmetric PEG derivatives can be easily synthesized . To demonstrate this, we prepared compounds 13 b – e (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation